ANALISIS KODE-MIXING DAN KODE-SWITCHING DALAM PERCAKAPAN MAHASISWA SEMESTER EMPAT PBSI UNIVERSITAS NURUL HUDA - Miftahul Hasanah; Vella Julia; Lutvi Qolbiyatu Zuhro NH; Sugiarti Sugiarti (Jurnal Padamu Negeri, 2025)
This study aims to analyze the phenomenon of code-mixing and code-switching that occurs aong 4th-semester students of the Indonesian Language and Literature Education Study Program (PBSI) at Universitas Nurul Huda. Using a descriptive quaitative approach, the research collects data through observation, conversation recordings, and interviews in campus environments as well as on social media. The findings indicate that PBSI students actively use intersentential code-mixing (between Indonesian and regional languages), intrasentential code-mixing (involving foreign languages), and mixed code-mixing. Meanwhile, code-switching occurs both internally (within the same language family) and externally (with foreign languages). Factors influencing these phenomena include the multilingual linguistik background of students, the influence of social edia and digital platforms, as well as expressive goals in communication. This research provides insights into the dynamics of language use in academic and social contexts, as well as the importance of linguistik awareness in Indonesian language education.